Biologia reprodutiva de fêmeas de laetacara araguaiae (labriformes: cichlidae) - Silva, Amanda Pereira dos Santos [UNESP] (2014)
Laetacara araguaiae is a species of south American ciclideo described in the Araguaia river basin, São Miguel do Araguaia, Goias, Brazil by Ottoni and Costa (2009). The description of reproductive phases is being performed some time ago with the analysis of the annual reproductive cycle, that is based on stages of gonadal maturation of analyzed species. The objective of this work was to describe morphologically the reproductive cycle of female L. araguaiae. Were collected from 80 females of L. araguaiae, in the period April/2012 to March/2013, in Two Streams, river Selviria, Mato Grosso do Sul, Brazil. The ovaries were processed, using techniques for light microscopy and transmission electron microscopy. Even were identified phases of the reproductive cycle that apply to females, gonadossomatico index (GSI) and size of first ovarian maturation. The oogenesis presented germinative epithelium with three types of oogonias and oocytes in phase of profase of meiosis for the formation of the ovarian follicles. Primary Growth with the presence of oocytes pre-vitelogenicos and oocytes cortical alveoli and secondary growth or vitelogenese, characterized by initial deposition of granules of yolk. The event which characterizes the maturation stage is the migration from the nucleus to the periphery of the oocyte toward through. The follicular suffered complex morphological changes along the stages of oocytes. In addition, for Laetacara araguaiae were defined five reproductive phases throughout the year: immature, development, able to spawning, regression and regeneration. The average length of first ovarian maturation was estimated at 2.0 cm standard length. The mature individuals (able to spawn) were captured from September to coincide with the seasons of spring and summer. The IGS showed high average values in phase of able to spawn (4,528) and the lowest average values in immature (0.502). The seasons of the year in which the individual is able ...